PERILAKU TIDAK MEMILIH PADA PEMILIHAN PENGHULU DI KEPENGHULUAN TELUK PIYAI KECAMATAN KUBU KABUPATEN ROKAN HILIR 2016 - Hidayatullah Husaini; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study, which is substantiated simultaneously in rural elections in 2016, according to Law No. 6 of 2014 Village. Penghulu elections are held at the same time as Bay Kepenghuluan Piyai Kubu District Rokan Hilir. At the time of the elections, the community's non-selective behavior was very high. Based on the background of the problem, the study aims to determine the reasons for Gulf Kepenghuluan communities mimilih no Piyai Kubu district Rokan Hilir on village headquarters at the same time in 2016. The research approach is used in this paper qualitative. Data mining is primary and secondary data. The data was collected on research information materials and documents. The data was analyzed in a descriptive manner.These findings suggest that socio-economic factors at higher education levels, as well as the causes of human behavior, have only been found by a few informants, and the majority of non-voters have caused low levels of education, low economic. Various perceptions make people more concerned with piyai rooms, such as work, rather than participating in the prince elections. Judging by the public psychological factors in the Gulf Kepenghuluan Piyai people tend to choose where the absence of emotional relationships with the potential prince, and high indifference to political activity that causes prejudice on the choices of the prince as something useless. It looks like a rational choice for factor people who are not allowed to vote because they consider going to choose the benefits and benefits. Thus, they are more concerned about job issues than at the polling station. Judging by the political confidence factor, people do not vote because it does not believe the government's performance kepenghuluan bay piyai and do not believe the mayor's nominee, so that the public is more concerned with the job, rather than going to the choice of the Prince of the Gulf of Kepenghuluan Piyai 2016.KEYWORDS: Not choosing behavior, choice of directors